Encyclopedia of Dr. Mahathir Bin Mohamad : prime minister of Malaysia - Hashim Makaruddin; Shayeb, Talaat El (Kuala Lumpur : Darul Fikir, 2004)
vol. 1. Islam and the Muslim ummah -- v. 2. The challenge Mahathir Mohamad -- v. 3. Asia : reflections on Asia a new deal for Asia -- v. 4. Globalisation smart partner ship and government -- v. 5. Malaysia -- v. 6. Globalisation and the new realities -- v. 7. Science, technology, and human rights -- v. 8. Politics, democracy, and the new Asia -- v. 9. Development and regional cooperation -- v. 10. Contemporary issues